Impact of Living Conditions on Online Education: Evidence from China - Jiafeng Gu (Sustainability, 2022)
Students need to maintain certain living conditions in order to pursue online learning at home. However, there is a lack of a scientific explanation for the extent to which students’ performance in online at-home education is influenced by living conditions. Students from 2002 low-income households in China were surveyed, and a multivariate logistic regression analysis was conducted in order to explore the impact of living conditions on online education. The results showed that, rather than computers and smartphones, broadband Internet at home can affect students’ performance in online learning. The larger the residence area, the better the children’s performance in at-home e-learning. Moreover, children living in dilapidated houses are unable to satisfactorily perform in an e-learning environment. Contrarily, children who live in families with separate rooms and tap water show better performances. Additionally, the performance will be worse in the case of unattended students. Furthermore, children from low-income and -status families in the community are often at a disadvantage in an at-home e-learning environment. Cognition regarding the connection between living conditions and online education can be crucial for the improvement of the living conditions of low-income families in order to achieve online education equity.